Making of audio compact disc : his embrace, her arrival. - Goh, Yee Lee. (2008)
The goals of this project are to produce a Mandarin pop album that is similar to commercial CDs, discover new talents in the local Mandarin pop music scene and for us to acquire skills in producing a music album.